Cybersecurity of freight information systems a scoping study (Transportation Research Board, Computer Science and Telecommunications Board, 2003)
Reviews trends in the use of information technology in the freight transportation industry. This book assesses the potential vulnerabilities to a cyberattack.
Keywords: Telecommunication -- Safety measures.; Freight and freightage -- Security measures.; elektronické knihy; electronic books